Integrating Islamic Economic Principles with National Development : Implications for Growth and Social Welfare in Indonesia (International Forum of Researchers and Lecturers, 2025)
This study examines the implications of Islamic economic philosophy on national economic growth, with a particular focus on Indonesia. The paper explores how key principles within Islamic economics, such as justice, equity, and the prohibition of usury (riba), contribute to fostering a more inclusive and sustainable economic framework. These principles, which aim to ensure wealth is fairly distributed and that financial transactions are ethical, offer solutions that can address inequalities and foster long-term economic development. By analyzing secondary data from governmental reports, institutional publications, and global economic trends, this study reveals that Islamic economic instruments such as zakat (charitable giving), waqf (endowment), and the prohibition of riba (interest) have played significant roles in wealth redistribution, poverty alleviation, and the promotion of social welfare in Indonesia. Zakat and waqf, in particular, have been instrumental in channeling resources to the underprivileged and marginalized communities, helping reduce the gap between the rich and the poor. The study also highlights how Islamic economic practices align with global sustainable development goals (SDGs), emphasizing their relevance in addressing pressing global challenges such as inequality, climate change, and financial inclusion. This alignment demonstrates that Islamic economics offers a framework that is not only culturally and religiously rooted but also adaptable to global economic objectives. Despite the promising impact of these principles, the study concludes that Indonesia has made progress but still faces challenges in fully realizing their potential. Key areas for improvement include enhancing the management of zakat and waqf, boosting the competitiveness of the halal economy, and strengthening the connection between Islamic finance and global financial systems. These areas require continued efforts and policy support to maximize the benefits of Islamic economic principles in driving sustainable national economic growth.